Pemberdayaan Ekonomi Masyarakat Melalui Bank Sampah: Studi Kasus Peran Mahasiswa UM Berau sebagai Fasilitator - Darmono Darmono (ECO-BUILD, 2025)
This qualitative case study aims to analyze the role of UM Berau students as facilitators in empowering the community economy through waste banks in Berau, as well as to identify supporting factors and challenges. Data were collected through in-depth interviews, participatory observation, and documentation involving student facilitators and community members. Thematic analysis revealed four main themes: the active role of students as agents of change (initiation, technical assistance, network facilitation), the economic impact on the community (increased income, potential for creative enterprises), the process of empowerment and joint learning (formation of independent groups, knowledge transfer), and challenges and hopes for sustainability (participation, infrastructure, support). The results indicate the central role of students in motivating, assisting, and connecting the community, which positively affects income improvement and entrepreneurial potential. The empowerment process takes place through the formation of independent groups and knowledge transfer. However, challenges related to participation and infrastructure need to be addressed. This study concludes that UM Berau students play a crucial role in empowering the community economy through waste banks, with the expectation that this program can be sustained and replicated.